The Impact of COVID-19 on Physical Performance and Mental Health—A Retrospective Case Series of Belgian Male Professional Football Players - Wagemans, Jente; Catteeuw, Peter; Vandenhouten, Jan; Jansen, Jordi; de Corte, Xander; Ceusters, Ciesse; Vissers, Dirk (Frontiers in Sports and Active Living, 2021)
Rationale As every season, physical performance of players of Royal Antwerp FC’s first team was regularly tested and mental well-being and mood were assessed during football season 2020-2021. Just like in the general population, several professional athletes were infected by SARS-CoV-2 during that season. COVID-19 is a complex disorder affecting multiple body systems, potentially damaging lungs, affecting the cardiovascular system or causing muscle weakness. Therefore, the impact of COVID-19 on performance was a major concern for the affected football players and their entourage. Objectives To retrospectively examine the influence of COVID-19 on physical performance and mental health in professional football athletes during the season 2020-2021. Methods Thirty-three professional athletes (age: 25.37 ± 4.11 years; height: 182.75 ± 7.62 cm; weight: 78.90 ± 8.97 kg) of a Belgian first division football club were assessed weekly during the 2020-2021 season. Weekly assessments comprised strength values of the hamstrings, hip abductors and hip adductors, jump performance, a modified Hooper questionnaire to assess mental status and nose swab PCR tests for COVID-19. Data analysis was performed from two weeks prior to COVID-19 contamination up to eight weeks after the first positive test. Post-hoc Bonferroni correction was applied when performing statistical analysis. Results Eleven players tested positive for COVID-19. Duration of contamination was 13 ± 7 days. There was no statistically significant difference before and after COVID-19 infection for jump performance, and adductor and abductor muscle strength (p >0.05). Functional hamstring strength improved significantly 2 weeks (MD: 41.48; 95%CI: -3.79 to 86.75; p= 0.009) and 4 weeks (MD: 34.76; 95%CI: -8.91 to 78.42; p= 0.019) after COVID-19, whereas mood (MD: -0.60; 95%CI: -1.46 to 0.26; p= 0.041), stress levels (MD: -0.83; 95%CI: -1.85 to 0.20; p= 0.020) and total wellness (MD: -2.41; 95%CI: -5.25 to 0.43; p=0.015) showed a significant reduction eight weeks after confirmed COVID-19. Conclusion Physical performance varied considerable across outcomes before and 8 weeks after COVID-19 contamination in a sample of first division football players. However, affected football players’ overall well-being, stress levels and mood diminished after a positive COVID-19 test.